2020
DOI: 10.14710/jitaa.45.3.214-221
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and chemical characteristics in egg albumen fermented by lactid acid bacteria

Abstract: Research on fermentation time and the addition of milk powder to egg albumen is still limited. The purpose of this study was to determine the antioxidant activity and chemical characteristics of fermented egg albumen using different levels of full cream milk powder and different microbial fermentation times. This study used a completely randomized factorial pattern design, 4 x 5 treatments with 4 replications. Research materials include egg albumen, full cream milk powder and mixed Lactic Acid Bacteria (L. bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Lactic acid bacteria (LAB) fermentation is the simplest and safest technology, which affects the protein structure by enzymatic action and acidification. Nahariah et al (2020) reported that Lactobacillus sp (LAB), consisting of L.bulgaricus, L.achidopillus , and Streptococcus thermophilous, egg proteins were used in egg protein fermentation to obtain HEPs with antioxidant activity [ 63 ]. PPPs were prepared by lactic acid bacteria ( S. thermophilus: L. bulgaricus 1:1) fermentation at 1% w / w PV, 42 °C, for 9 h, and found that its calcium-binding capacity (NaOH consumption of 0.9 mL) was enhanced compared to the PPPs produced by enzymatic digestion (NaOH consumption of 2.85 mL) [ 64 ].…”
Section: Bioactive Peptides Derived From Hen Egg Proteinsmentioning
confidence: 99%
“…Lactic acid bacteria (LAB) fermentation is the simplest and safest technology, which affects the protein structure by enzymatic action and acidification. Nahariah et al (2020) reported that Lactobacillus sp (LAB), consisting of L.bulgaricus, L.achidopillus , and Streptococcus thermophilous, egg proteins were used in egg protein fermentation to obtain HEPs with antioxidant activity [ 63 ]. PPPs were prepared by lactic acid bacteria ( S. thermophilus: L. bulgaricus 1:1) fermentation at 1% w / w PV, 42 °C, for 9 h, and found that its calcium-binding capacity (NaOH consumption of 0.9 mL) was enhanced compared to the PPPs produced by enzymatic digestion (NaOH consumption of 2.85 mL) [ 64 ].…”
Section: Bioactive Peptides Derived From Hen Egg Proteinsmentioning
confidence: 99%